Perception of job seekers towards innovative e-recruitment - MONICA, DR. BENITA. S.; PRIYUSHA K, MS. THOSHINI (The journal of contemporary issues in business and government, 2020)
The increase in recruitment activities using the Internet, especially during the pandemic, result in financial savings of up to 90% of the costs incurred in traditional recruitment.The objective of the study is to understand the perception of job seekers regarding the usefulness of E-recruitment. Descriptive research is used in the study and sampling method used is convenience sampling. The sample size of the study is 100 and data is collected through a structured questionnaire. The results prove that factors under perception of E-recruitment are information, effectiveness and efficiency, usage of site, social media, job availability, decision making, internet information and service. It states that there is no significant difference between the demographic variables and perception of E-recruitment in job seekers